2000
DOI: 10.1002/1098-2825(20001212)14:6<265::aid-jcla3>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Reference distributions for the positive acute phase proteins, α1‐acid glycoprotein (orosomucoid), α1‐antitrypsin, and haptoglobin: A comparison of a large cohort to the world’s literature

Abstract: Limiting bedside use of positive acute phase protein measurements (alpha1-acid glycoprotein (orosomucoid), alpha1-antitrypsin, and haptoglobin) has been the lack of satisfactory methods for quantifying serum levels and a credible reference material. Great strides have been made in the last few years. The remaining barrier to more relevant and cost-effective use of serum protein data for diagnosis and prognosis is the availability of reliable reference intervals from birth to old age for both males and females.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…SERPINA-1 is synthesized by the liver, macrophages neutrophils and also by trophoblast 41. Increases in serum SERPINA-1 occur in diseases such as rheumatoid arthristis, vasculitis, infections and other diseases associated with an inflammatory component 42. Interestingly, studies have shown that even minor increases in levels of serum SERPINA-1 are associated with development of arterial hypertension and an increased risk of cardiovascular disease 43, 44.…”
Section: Discussionmentioning
confidence: 99%
“…SERPINA-1 is synthesized by the liver, macrophages neutrophils and also by trophoblast 41. Increases in serum SERPINA-1 occur in diseases such as rheumatoid arthristis, vasculitis, infections and other diseases associated with an inflammatory component 42. Interestingly, studies have shown that even minor increases in levels of serum SERPINA-1 are associated with development of arterial hypertension and an increased risk of cardiovascular disease 43, 44.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the methods used to search for relevant publication were the same as for the previous studies (1)(2)(3)(4)(5)(6) with the key-word headings and the analyte specific terms using PubMed (http://www.ncbi.nlm.nih. gov/PubMed) and MEDLINE CD-ROM searches (OVID Technologies, New York, NY).…”
Section: Materials and Methods Identification Of Published Reference Datamentioning
confidence: 99%
“…SERPIN1 increases in several diseases with an inflammatory component [43]. Even minor increases of this protein are associated with arterial hypertension and higher risk of cardiovascular disease [44], both related to IUGR at adult ages.…”
Section: Biological Significance Of the Proteins Characteristic Of Iumentioning
confidence: 99%